2022
DOI: 10.2147/jbm.s346904
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype, Allele and Genotype Frequency of ABO and Rhesus D Blood Groups of Blood Donors at the North Gondar District Blood Bank, Northwest Ethiopia

Abstract: Background: Knowledge of the ABO and RhD group distribution is essential for blood banks inventory and assuring quality blood transfusion services. The objective of this study was to determine the frequency of ABO and RhD phenotype, allele, and genotype among blood donors at North Gondar District Blood Bank from 2010 to 2012, Northwest Ethiopia. Methods: The data of the current study were obtained from registration logbooks of blood donors registered. The ABO and RhD grouping was done by using commercially ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…However, studies conducted in other countries reported a slightly higher proportion of female blood donors compared to Indian studies. Iyiola et al [ 7 ] from Nigeria reported 47.1% of female blood donors and Woldu et al [ 8 ] from Ethiopia reported 17.9% of female blood donors.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies conducted in other countries reported a slightly higher proportion of female blood donors compared to Indian studies. Iyiola et al [ 7 ] from Nigeria reported 47.1% of female blood donors and Woldu et al [ 8 ] from Ethiopia reported 17.9% of female blood donors.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 10–15 The proportion of the “O” blood group ranged from 21.67% 16 to 47.04%. 15 On the other hand, the “AB” blood group was the least prevalent blood group type, which ranged from 2.87% 12 to 24.7%. 16 The Rh-D positive blood group was the most common, accounting for 92.77% 11 to 60.13% of the population.…”
Section: Introductionmentioning
confidence: 99%
“…On comparing allele frequencies of different studies world-wide [24,25,[29][30][31][32], we found that allele frequency of I O in ABO & I D in Rh blood group system is highest across the world (Table 6). Thus our findings are similar to other studies.…”
Section: Discussionmentioning
confidence: 98%
“…We compared ABO & Rh (D) distribution across different states of India [3,[10][11][12][13][14][15][16][17][18][19][20] ( The distribution of ABO blood group varies across neighbouring [21][22][23] & other countries [24][25][26][27][28] of the world as seen in Table 5. In India O & B phenotypes are common; whereas in America [27] & Europe [28] O & A phenotypes are common.…”
Section: Discussionmentioning
confidence: 99%